(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
Margaret Atwood’s Oryx and Crake (2003) is a postapocalyptic novel set in the Maddaddam trilogy in which the "flood"—a man-made virus—has almost completely wiped out human life. Atwood uses the story of Snowman, the last human on Earth, and his struggle to survive in a difficult biological and ecological environment to attack present social, political, and economic structures, as well as traditional Western concepts of subjectivity. In this paper, the focus is mainly shed on the distribution of power in the novel. The research benefits from Foucault’s concept of “Bio politics” which